Simultaneous Multislice Diffusion-Weighted Imaging of the Kidneys at 3 T. Issue 4 (April 2020) - Tavakoli, Andrej; Krammer, Julia; Attenberger, UIrike I.; Budjan, Johannes; Stemmer, Alto; Nickel, Dominik; Kannengiesser, Stephan; Morelli, John N.; Schoenberg, Stefan O.; Riffel, Philipp
Abstract : Purpose: The aim of this study was to compare respiratory-triggered diffusion-weighted imaging with simultaneous-multislice acceleration (SMS-RT-DWI) to a standard free-breathing echoplanar DWI (s-DWI) for 3 T renal imaging with respect to image quality and artifacts. Materials and Methods: A total of 40 patients who had undergone renal magnetic resonance imaging were included in this retrospective analysis of a prospectively planned cohort study. All examinations were performed on a 3 T whole-body magnetic resonance system. Both s-DWI and SMS-RT-DWI were obtained and images were independently reviewed by 2 radiologists on a 5-point Likert scale with respect to overall preference and image quality, renal edge and parenchymal sharpness, cortico-medullary differentiation, and sequence-related artifacts. Furthermore, discernibility of renal lesions was assessed. The signal-to-noise ratio (SNR) was measured from SNR maps. The derived mean apparent diffusion coefficients were also compared. Qualitative parameters were assessed with the Wilcoxon rank-sum test, and quantitative parameters, with the Student t test. Results: Overall image quality, renal edge, and parenchymal sharpness of SMS-RT-DWI were rated as superior to s-DWI by the readers, with fewer sequence-related artifacts ( P < 0.01 for all). Lesion discernibility was significantly improved for SMS-RT-DWI ( P < 0.01). Both readers preferred SMS-RT-DWI to s-DWI in all cases (40/40). The acquisition time for SMS-RT-DWI was 30% shorter than for s-DWI. Mean SNR heterogeneity of SMS-RT-DWI at b = 800 s/mm 2 was statistically significantly lower than s-DWI, whereas mean SNR was significantly higher for SMS-RT-DWI. Mean apparent diffusion coefficient values from both sequences were comparably homogeneous throughout the kidneys. Conclusion: Simultaneous multislice DWI of the kidney at 3 T with respiratory triggering yields substantially improved image quality and lesion discernibility compared with standard single-shot echoplanar DWI with a 30% reduction in scan acquisition time.